The use of ChatGPT in the digital era: Perspectives on chatbot implementation (Journal of Applied Learning and Teaching, 2023)
The rapid advancement of technology has led to the integration of ChatGPT, an artificial intelligence (AI)-powered chatbot, in various sectors, including education. This research aims to explore the perceptions of educators and students on the use of ChatGPT in education during the digital era. This study adopted a qualitative research approach, using in-depth interviews to gather data. A purposive sampling technique was used to select ten educators and 15 students from different academic institutions in Krabi, Thailand. The data collected was analysed using content analysis and NVivo. The findings revealed that educators and students generally have a positive perception of using ChatGPT in education. The chatbot was perceived to be a helpful tool for providing immediate feedback, answering questions, and providing support to students. Educators noted that ChatGPT could reduce their workload by answering routine questions and enabling them to focus on higher-order tasks. However, the findings also showed some concerns regarding the use of ChatGPT in education. Participants were worried about the accuracy of information provided by the chatbot and the potential loss of personal interaction with teachers. The need for privacy and data security was also raised as a significant concern. The results of this study could help educators and policymakers make informed decisions about using ChatGPT in education.